(untitled) (Malaysian Journal of Learning and Instruction, 2014)
Purpose â€“ This study was conducted to examine relationships between perceived social support, university adjustment and academic achievement of fi rst semester students enrolled in various undergraduate programs in a Malaysian public university. Methodology â€“ This study employed a quantitative approach with a descriptive correlation design to address the research objectives. The adapted version of the â€œInterpersonal Support Evaluation Listâ€ (1985) and the â€œStudent Adaptation to College Questionnaireâ€ (1999) were used to assess studentsâ€™ perceived social support and university adjustment respectively. A total of 250 fi rst year undergraduates were selected as respondents using cluster random sampling technique. Findings â€“ Findings revealed a signifi cant and positive relationship between studentsâ€™ perceived social support and their overall university adjustment as well as all the four adjustment dimensions namely academic adjustment, social adjustment, personal-emotional adjustment, attachment to university, and academic achievement. Results also indicated that studentsâ€™ overall university adjustment and academic achievement were signifi cant and positively predicted by social support. Significance â€“ This study provides important evidence for undergraduates, lecturers, university administrators, and the community at large regarding the important role of social support in university adjustment and academic performance. It is suggested that a university should provide support services to assist new undergraduates to overcome their adjustment problems.